Quintiles IPO - Stowell, David (David P.); Setia, Vishwas (London : SAGE Publications Ltd, 2017)
Quintiles Transnational Holdings Inc., the largest global provider of biopharmaceutical development and commercial outsourcing services, grew its revenue at a CAGR of 7.3% and EBITDA at 13.9% between 2008 and 2012.The case is set in December 2012April 2013, when the majority of the firm was owned by founder Dennis Gillings and four private equity firms (Bain Capital, TPG Capital, 3i Capital and Temasek Life Sciences) after it was taken private in a management-led buyout in 2003 and a subsequent buyout in 2008. Five years after the second buyout, the private equity firm owners were looking to monetize their positions and considered different strategic alternatives: M&A sale to strategic or financial buyers, IPO, or capital restructuring through special dividends.Students will step into the role of an associate at the lead investment bank working with Quintiles. They must consider the case information and determine an IPO strategy, process, potential conflicts, and valuation.
Originally published: Stowell, D. P., & Setia, V. (2014). Quintiles IPO. 5-413-756 Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Quintiles Transnational Corporation -- Case studies; Pharmaceutical industry -- United States -- Case studies; Biopharmaceutics -- United States -- Case studies; Business enterprises -- Valuation -- United States -- Case studies; Consolidation and merger of corporations -- United States -- Case studies